Cooling‐activated dorsomedial hypothalamic BDNF neurons control cold defense in mice. Issue 3 (25th August 2022) - Zhou, Qian; Liu, Changhao; Chen, Ting; Liu, Yanyang; Cao, Ren; Ni, Xinyan; Yang, Wen Z.; Shen, Qiwei; Sun, Hongbin; Shen, Wei L.
Abstract: BDNF and its expressing neurons in the brain critically control feeding and energy expenditure (EE) in both rodents and humans. However, whether BDNF neurons would function in thermoregulation during temperature challenges is unclear. Here, we show that BDNF neurons in the dorsomedial hypothalamus (DMH BDNF ) of mice are activated by afferent cooling signals. These cooling‐activated BDNF neurons are mainly GABAergic. Activation of DMH BDNF neurons or the GABAergic subpopulations is sufficient to increase body temperature, EE, and physical activity. Conversely, blocking DMH BDNF neurons substantially impairs cold defense and reduces energy expenditure, physical activity, and UCP1 expression in BAT, which eventually results in bodyweight gain and glucose/insulin intolerance. Therefore, we identify a subset of DMH BDNF neurons as a novel type of cooling‐activated neurons to promote cold defense. Thus, we reveal a critical role of BDNF circuitry in thermoregulation, which deepens our understanding of BDNF in controlling energy homeostasis and obesity. Abstract : In this study, we investigated the function of dorsomedial hypothalamic BDNF neurons (DMH BDNF neurons) in thermoregulation in mice. Calcium activity recordings showed DMH BDNF neurons are activated by ambient cooling. Activation of DMH BDNF neurons or the GABAergic subpopulations increases body temperature, energy expenditure, and physical activity. Conversely, blocking DMH BDNF neurons impairs cold defense and reduces UCP1 expression in BAT, resulting in bodyweight gain. Thus, our data indicated that DMH BDNF neurons function as previously unidentified cooling‐activated neurons in the brain to promote cold defense, which deepens our understanding of BDNF in controlling energy homeostasis and obesity.